PROFITABILITY OF ISLAMIC COMMERCIAL BANKS: A STUDY OF INTERNAL AND MACROECONOMIC FACTORS - Aufrieda Artsiana Dewi; Anggraeni Anggraeni (JURNAL PROFIT, 2025)
This study analyzed the impact of internal and external factors on the profitability of Islamic commercial banks in Indonesia, measured by ROA. Using quarterly financial data from 2019 to 2024, with 224 valid observations, the analysis focused on CAR, FDR, NPF, BOPO, bank size, GDP, and inflation. The findings show that internal factors significantly influence profitability, with NPF and BOPO negatively affecting ROA, while larger bank size correlates with lower profitability due to higher operational costs. External factors like GDP and inflation had no significant impact on ROA. F-test and R² results confirm the model’s statistical significance and explanatory power. The study highlights the importance of internal management strategies, recommending improvements in asset quality and operational efficiency to boost financial performance.